Neuro-biomechanics of maximum velocity sprinting - Seagrave, L.; Mouchbahani, R.; O'Donnell, K. (New Studies in Athletics, 2009)
The most widely used technical model of the running stride comprises three phases: the Drive, the Swing and the Lift. How-ever, using this model, and emphasising the development of strength to meet the aim of applying more force to the ground, many coaches neglect the neuro-physiological aspects of sprinting technique and may limit their athletes' performance in the Maximum Velocity Phase of the 100 metres, known as the key to success in the event A more contemporary model, taught in the IMF Coaches Education and Certification System and demonstrated by the world's fastest Sprinters, provides better understanding of high-speed running mechanics and the implications for generating and maintaining greater maximum velocity. According to the authors, this model can be developed using six reference points or foci: Body Position, Recovery Mechanics, Transition Phase, Ground Preparation Phase, Ground Phase, and Arm Action. With video captures of former world record holder Asafa Powell (JAM) in competition to illustrate their points, they discuss each of the foci in detail. They also explain how the quality of any phase in the cyclical movement of the sprinting stride is determined by the quality of the phase that immediately precedes it. They conclude by stating that retaining the traditional model limits the performance Potential of the athlete.